2021
DOI: 10.7554/elife.67437
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative mapping of human hair greying and reversal in relation to life stress

Abstract: Background:Hair greying is a hallmark of aging generally believed to be irreversible and linked to psychological stress.Methods:Here, we develop an approach to profile hair pigmentation patterns (HPPs) along individual human hair shafts, producing quantifiable physical timescales of rapid greying transitions.Results:Using this method, we show white/grey hairs that naturally regain pigmentation across sex, ethnicities, ages, and body regions, thereby quantitatively defining the reversibility of greying in human… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 123 publications
(159 reference statements)
2
39
0
1
Order By: Relevance
“…These preserved MeSCs with normal morphology and functionality can recolor newly regenerated hairs in next hair cycle. Consistently, a more recent study in humans showed that hair graying and hair recoloring can occur in parallel with stress exposures in young individuals of 9-39 years old (Rosenberg et al, 2021). Hair graying and recoloring can be observed within a single hair shaft in humans but not in mice.…”
Section: Neural Microenvironmentsupporting
confidence: 61%
“…These preserved MeSCs with normal morphology and functionality can recolor newly regenerated hairs in next hair cycle. Consistently, a more recent study in humans showed that hair graying and hair recoloring can occur in parallel with stress exposures in young individuals of 9-39 years old (Rosenberg et al, 2021). Hair graying and recoloring can be observed within a single hair shaft in humans but not in mice.…”
Section: Neural Microenvironmentsupporting
confidence: 61%
“…Mitochondria play a vital role in skin and there exists increasing evidence that mitochondrial dysfunction and oxidative stress are key features in senescence and aging skin with direct links to skin and hair aging phenotypes (e.g., uneven pigmentation and hair graying). 68,212,213 Melatonin is found in especially high concentrations in mitochondria, 214,215 where it is transported to, 216 synthesized, 217 or metabolized. 92 Within mitochondria, cytochrome c converts melatonin to its potent antioxidant metabolite, AFMK, 91 and its secondary product, AMK in the presence of H 2 O 2 .…”
Section: Melatonin Regulates Senescence Progression and Promotes Mito...mentioning
confidence: 99%
“…Hair graying is usually a progressive process starting from middle age. Color of a single hair can sometimes swing between black and white (Rosenberg et al, 2021), suggesting that it is a reversible process at least in early stages. Aging-related hair graying largely attributes to loss of melanocytes and melanocyte stem cells (MeSCs) (Nishimura et al, 2005).…”
Section: Pigment Changes During Agingmentioning
confidence: 99%
“…This can be resulted from the aging of HFSCs that forms the niche environment of MeSCs . It was also found that stress-induced neuronal activity can cause hair graying by norepinephrine mediated MeSCs loss (Rosenberg et al, 2021;Zhang et al, 2020a). Notably, human hair graying is not only a color change but also associated with alterations in the biophysical properties and growth rate of the hair shaft (Van Neste and Tobin, 2004), implicating profound changes in the graying HF's epithelial lineage.…”
Section: Pigment Changes During Agingmentioning
confidence: 99%